Differences in unintended pregnancy, contraceptive use and abortion by HIV status among women in Nigeria and Zambia (2014)
CONTEXT: Sub-Saharan Africa is burdened by high rates of unintended pregnancy and HIV. Yet little is known about the relationship between these two health risks in the region. Understanding the associations between HIV status and pregnancy decision making may benefit strategies to reduce unintended pregnancy. METHODS: In 2009–2010, household-based surveys of 1,256 women in Nigeria and 1,280 women in Zambia collected information on social and demographic characteristics, unintended pregnancy, contraceptive use, abortion and self-reported HIV status. Multivariate models were used to examine the association of reported HIV status with nintended pregnancy and abortion in the five years preceding the survey and with contraceptive use at the time of conception. RESULTS: HIV-positive and HIV-negative women did not differ in their odds of unintended pregnancy or of having an abortion. However, HIV-positive women were more likely than HIV-negative women to have been using a contraceptive at the time their unintended pregnancy was conceived (odds ratio, 3.2). Women who did not know their HIV status were less likely than HIV-negative women to report an unintended pregnancy (0.6). However, they were also less likely than HIV-negative women to have been using a contraceptive at the time of conception (0.5). CONCLUSION: HIV-positive women may be making greater efforts than HIV-negative women to prevent unintended pregnancy, but with less success. Efforts should be made to improve access to effective contraceptive methods and counseling for all women, and for HIV-positive women in particular.